TRANSLATION PROCEDURESIN PATIENT INFORMATION LEAFLETS - Rahmawati Rahmawati; Busmin Gurning; Sri Minda Murni (LINGUISTIK TERAPAN, 2018)
The aims of this study were to find out the types of translation procedures in Patient Information Leaflets, to describe the realization of translation procedures and to explain about the reason of certain translation procedures realized in Patient Information Leaflets.The research was conducted by using qualitative descriptive design. The data of this study was translation unit that consists of words, phrases, clauses and sentences in Patient Information Leaflets in two versions, English as the source text and Bahasa Indonesia as the target text. The data was analyzed by using the theory of Translation Procedures based on (Vinay and Darbelnet, 2000) to find the types, realization and the reason of certain translation procedures were used in Patient Information Leaflets. The results of the study were; there were eight types of translation procedures in patient information leflets namely borrowing, calque, literal translation, transposition, modulation, equivalent, deletion and mixing procedures, there were some realization of translation procedures in patient information leaflets, and there were seven reasons behind the realization of translation procedures. Keywords: Translation, Translation Procedures, Patient Information Leaflets, English and Bahasa Indonesia.